MATHEMATICAL COMMUNICATION ABILITY AND CURIOSITY ATTITUDE THROUGH PROBLEM BASED LEARNING AND COGNITIVE CONFLICT STRATEGY BASED ON ACADEMIC LEVEL: A STUDY IN NUMBER THEORY - Zetriuslita, .; Wahyudin, Jarnawi (PEOPLE: International Journal of Social Sciences, 2018)
The aim of this research is to examine the achievement and improvement of students’ Mathematical Communication Ability (MCA) and Curiosity Attitude (CA) through Problem-Based Learning Model and Cognitive Conflict Strategy (PBLCCS) and Explicit Direct Instruction (EDI). Adopting a quasi-experimental mixed method with pretest-posttest control group design and sequential explanatory strategy, the study population consists of undergraduate students of Mathematics Education Study Program at a private Islamic University in Riau of Sumatra Indonesia, academic year 2015/2016 in course subject of Number Theory. Quantitative data were collected from essay tests, questionnaires and interview sheets whereas observation sheets were used to generate qualitative data. The findings show that there is (1) no difference in Mathematical Communication Ability (MCA) between students tought by Problem-Based Learning and Cognitive Conflict Strategy (PBLCCS) and Explicit Direct Instruction (EDI) based on academic levels (high, medium, low); (2) no difference in Mathematical Curiosity Attitude (CA) between those who have been taught by PBLCCS and EDI based on academic levels (high, medium, low) despite students’ mistakes in mathematical communication; (3) PBLCCS has not been able to improve students’ curiosity in learning mathematics; (4) Worksheet cannot optimally improve students’ MCA and CA.